The Attractiveness Of Public Employment: A Study Of Perception Among Final Year University Students In Peninsular Malaysia - Woo , Kuan Heong (2010)

(untitled)
Dissatisfaction with the performance of the Malaysian civil service has called into question the ability of the civil service to attract needed manpower. This study uses a clustered-stratified random sample of 1,200 final year students of four public universities to examine the attractiveness of public employment to graduates and the ability of the civil service to attract graduate manpower for ensuring capacity and representativeness.